Virus-Host Cell Interactions - Hoenen, Thomas; Groseth, Allison (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Viruses are obligate intracellular parasites, and their biology is closely interlinked with that of their host cells. However, this relationship is two-sided. Virus-host cell interactions are clearly essential to allow viruses to facilitate their life cycles, but they also give the host cell a chance to recognize and combat virus infections. This Special Issue of Cells compiles review papers on emerging themes related to virus-host cell interactions of RNA viruses, including mechanistic details of virus uncoating, new insights into the nature and function of viral replication compartments, and the role of RNA methylation in the virus life cycle. This is complemented by primary research papers addressing virus-host cell interactions from diverse perspectives.